Longitudinal cascades of Alzheimer disease biomarkers across the entire adult lifespan among cognitively normal adults. (31st December 2021) - Xiong, Chengjie; Luo, Jingqin; Agboola, Folasade; Grant, Elizabeth A.; Masters, Colin L.; Albert, Marilyn S.; Johnson, Sterling C.; McDade, Eric; Fagan, Anne M.; Benzinger, Tammie L.S.; Hassenstab, Jason; Bateman, Randall J.; et al.
Abstract: Background: The temporal cascade of Alzheimer disease (AD) biomarkers among cognitively normal individuals, including cerebral spinal fluid (CSF) Aβ42, Aβ40, total tau (Tau) and phosphorylated tau (pTau), standardized uptake value ratio (SUVR) from the molecular imaging of cerebral fibrillar β‐amyloid with positron emission tomography (PET) using the [ 11 C] benzothiazole tracer, Pittsburgh Compound‐B (PiB), magnetic resonance imaging (MRI)‐based hippocampal volume and cortical thickness, and cognition has been hypothesized, but not yet fully tested with longitudinal data. Method: Leveraging a large harmonized database of 2703 cognitively normal individuals 18 to 103 years of age from 8 longitudinal studies with a median follow up of 5∼6 years, we estimated the longitudinal trajectories of all major AD biomarkers as functions of baseline age, located the age window at which the longitudinal change accelerated by comparing it across adjacent age bins, and examined possible modifying effects of apolipoprotein E ( APOE ) genotypes. Result: Participants 18 to 45 years of age at baseline exhibited 'learning effects' on both cognition and all but the MRI‐based biomarkers. The earliest acceleration of longitudinal change occurred for CSF Aβ42 and Aβ42 /Aβ40 ratio at the baseline age of 45 to 50 years, followed by hippocampal volume at the baseline age of 55 to 60 years, further by CSF Tau, PET PiB mean cortical SUVR, cortical thickness, and cognition at the baseline age of 65 to 70 years. The accelerated longitudinal changes remained in the covariate‐adjusted analyses. APOE ε4 modified the observed 'learning effects' from 18 to 45 years. Further, there was preliminary evidence that APOE ε4 carriers may have experienced the first significant acceleration of the longitudinal change in almost all major AD markers within the baseline age window of 45 to 55 years, whereas among APOE ε4 non‐carriers, only PiB PET SUVRs and cortical thickness and the cognitive composite showed the earliest longitudinal acceleration of change at the same baseline age interval. Conclusion: Our results characterize the temporal cascades of longitudinal changes for all major AD biomarkers across entire adult lifespan, and address the modifying effect of APOE ε4. These findings may better inform the design of prevention trials on AD.